1995
DOI: 10.1164/ajrccm.152.2.7633699
|View full text |Cite
|
Sign up to set email alerts
|

Effects of PEEP on liver arterial and venous blood flows.

Abstract: Total venous return decreases with positive end-expiratory pressure (PEEP). It is likely that the liver plays an important role in this response, either through the development of an increase in venous resistance or through an increase in the venous backpressure at the outflow end of the liver. In addition, hepatic arterial flow is reported to be selectively decreased by the application of PEEP. Therefore, to clarify the effects of PEEP on liver hemodynamics, we generated pressure-flow (P-Q) relationships in b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
3
2

Year Published

1996
1996
2012
2012

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(60 citation statements)
references
References 30 publications
(45 reference statements)
3
52
3
2
Order By: Relevance
“…Other possible mechanisms for the drop in Q VR include increased resistance to venous return and decrease the maximal value of venous return (increased Pcrit) [16,18] due to venous geometry distortion at the entrance of the venae cavae into the thorax [19] or further upstream in the portal circulation (i.e. compression of the liver by diaphragmatic descent) [20]. Geometric alteration of the inferior vena cava (ICV) at its point of entry the thorax is not restricted to positive pressure ventilation.…”
Section: Lung Inflation and Hemodynamicsmentioning
confidence: 99%
“…Other possible mechanisms for the drop in Q VR include increased resistance to venous return and decrease the maximal value of venous return (increased Pcrit) [16,18] due to venous geometry distortion at the entrance of the venae cavae into the thorax [19] or further upstream in the portal circulation (i.e. compression of the liver by diaphragmatic descent) [20]. Geometric alteration of the inferior vena cava (ICV) at its point of entry the thorax is not restricted to positive pressure ventilation.…”
Section: Lung Inflation and Hemodynamicsmentioning
confidence: 99%
“…This compression is independent from any effect on the generalized abdominal pressure produced by diaphragmatic descent, since it also occurs with an open abdomen [50]. The compression on the liver surface from the downward displacement of the diaphragm could reduce the diameter and/or the number of the perfused sinusoidal channels, and cause an increase in splanchnic venous resistance, and a decrease in splanchnic venous return [51], simulating an abdominal zone III. However, MURCIANO et al [52] showed that in most COPD patients, there is little change in gastric pressure during spontaneous respiration.…”
Section: Abdominal Pressurementioning
confidence: 99%
“…The decrease in CO is accompanied by an increase in heart rate and a decrease in arterial pressure [30, 33]. Meanwhile, the rise in intra-alveolar pressure, the subsequent rise in pulmonary vascular resistances and difficulties with venous return precipitate increases in CVP [11, 31]and venous portal pressure [6, 8, 15, 21]. In effect, a state of relative hypovolaemia [9]is produced with PEEP.…”
Section: Discussionmentioning
confidence: 99%
“…However, these favourable effects are accompanied by the haemodynamic side effects of increased intrathoracic pressure and reduction in cardiac output (CO) [30, 37, 39]. Reduction in hepatic [8, 15, 41], renal and gastric fundal [4, 31]blood flow has been demonstrated, but little is known about its effects on gastrointestinal parietal perfusion or oxygen delivery, nor about its implications in anastomotic healing.…”
Section: Introductionmentioning
confidence: 99%